FORMATION OF STUDENTS' READINESS FOR CREATIVITY PROFESSIONAL ACTIVITY - V.V. Ivanova (Academy of Cognitive and Natural Sciences, 2008)
The article deals with various problems of forming of readiness for іn ative pedagogical activities, and making optimum conditions of pedagogical process